Radiofrequency catheter ablation for re-do procedure after single-shot pulmonary vein isolation with pulsed field ablation for paroxysmal atrial fibrillation: case report - Yang, Xinyan; Lin, Mingjie; Zhang, Yan; Wang, Juntao; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2024)
Background Catheter ablation is frequently used to manage recurrent atrial fibrillation (AF) resistant to drug therapy, with pulmonary vein isolation (PVI) as a key tactic. Pulsed field ablation (PFA) has emerged as an innovative technology for PVI but poses challenges for redo procedures. Case presentation We report on a 73-year-old female patient who experienced recurrent AF after initial successful PVI using a novel PFA technology and subsequently underwent radiofrequency catheter ablation during a repeat intervention. The reconnection of pulmonary veins was discovered primarily in the anterior region of the right superior PV and the superior portion of the left superior PV. An anatomically-based segmental approach and larger circumferential PVI, followed by additional linear ablations at non-PV trigger sites, proved decisive in preventing further recurrence of atrial tachycardia. Conclusion While PFA exhibits promise as a secure and efficient modality for PVI, it necessitates excellent contact quality to ensure lasting results. For patients experiencing AF recurrences post-PFI, expanded strategies incorporating both comprehensive PVI and linear ablations at targeted non-PV sites might enhance treatment outcomes.